Christherre-Chronik nieznanego autora w rękopisie zakonu krzyżackiego z Biblioteki Uniwersyteckiej w Toruniu - Olinski, Piotr (Folia Toruniensia, 2011)
The copy of Christherre-Chronik in the University Library of Nicolaus Copernicus University in Torun is one of 95 copies of the work preserved and available now in Europe. As it was settled by R. Plate, the manuscript was created at the end of the 14th century, probably outside the Teutonic Order. Apart from Christherre-Chronik the manuscript includes The Chronicle of the World by Rudolf von Ems. The manuscript was kept in Tapiau between 1468 and 1474, and in 1541 in Königsberg. Probably in Tapiau shortly before 1541 the inner sides of the cover were lined with documents from Ostroda. It seems that originally the code was kept in Malbork, and not in the castle in Ostroda as it was previously thought. Acquiring Christherre-Chronik by the Teutonic Knights may be the evidence of the reception of the knowledge of the Old Testament, which became quite common among some groups in the Teutonic Order in the face of the crisis in the Teutonic State from the turn of the 14th and 15th centuries.